The Influence of Competency, Motivation, and Work Discipline on Employee Performance in the Trade and Industry Department of Gowa Regency - Andi Tenri Unga; Sitti Nurbaya; Nurinaya (www.amertainstitute.com, 2025)
This research aims to examine the effect of motivational competence and work discipline on the performance of employees at the Trade and Industry Office of Gowa Regency. Employing a quantitative research approach, the study involved a sample of 34 employees with civil servant (PNS) and government contract (PPPK) status. Data were collected through a questionnaire consisting of several statements, utilizing both primary and secondary sources. The research instrument adopted the Likert scale for measurement. Statistical analysis was conducted using the Statistical Package for the Social Sciences (SPSS) version 26. The findings reveal that competence, motivation, and work discipline positively and significantly influence employee performance.